Migration status and healthcare seeking behaviours among the Chinese labor-force: a nationally representative study - Hui Zhang; Lishuo Shi; Li Ling; Boli Peng (BMJ Open)
Objectives We aimed to analyse the healthcare seeking behaviours (HSB) of populations with different migration status and examine the relationship between migration status and HSB.Design A secondary analysis of cross-sectional data of China Labor-force Dynamics Survey wave 2016, which was conducted by the Sun Yat-sen University every 2 years since 2010.Setting 29 provinces/cities/autonomous regions in mainland China, excluding Tibet and Hainan province.Participants 3522 respondents in a condition in the previous 2 weeks or during the last 12 months were analysed.Main outcome measures The migration status included internal migrants (IMs), returned population, rural residents and urban residents. The HSB including health services utilisation and choice of health facilities for their health services. Multivariable logistic regressions were used to examine the association between migration status and HSB.Results 2193 and 1898 of 3522 respondents were in need of outpatient services (having a condition in the previous 2 weeks) or inpatient services (being asked to use the inpatient services during the last 12 months). Compared with urban residents, the returned population (OR=0.66, 95% CIs 0.49 to 0.89) and rural residents (OR=0.65, 95% CIs 0.51 to 0.82) were less likely to have an unmet need for outpatient services. The latter tended to choose lower-level hospitals, while the IMs preferred the lowest-level healthcare facilities for health services. After controlling for confounding factors, the results above did not reach any statistical significance.Conclusion Association between migration status and HSB might be through enabling resource and needs. Returned population, IMs and rural residents tended to choose low-level hospitals for their health service needs, but this association was mainly associated with their poorer social and economic resources. Improving their social and economic resources would be helpful for reducing the barriers of HSB.